2009
DOI: 10.1097/bcr.0b013e3181ac0003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Motor Imagery in the Rehabilitation of Burn Patients

Abstract: Although there is ample evidence that motor imagery (MI) improves motor performance after CNS injury, it is still unknown whether MI may enhance motor recovery after peripheral injury and most especially in the rehabilitation of burn patients. This study aimed to investigate the effects of a 2-week MI training program combined with conventional rehabilitation on the recovery of motor functions in handed burn patients. Fourteen patients admitted to the Medical Burn Center were requested to take part in the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…The association of MI with real practice led to better efficiency than in the ctrl group. Although the two groups achieved comparable final performance, learning was nevertheless facilitated during the early phases, as previously shown by Guillot et al, (2009). [39] Mulla et al (2012) observed that mental training alone cannot replace conventional training.…”
Section: Resultssupporting
confidence: 54%
“…The association of MI with real practice led to better efficiency than in the ctrl group. Although the two groups achieved comparable final performance, learning was nevertheless facilitated during the early phases, as previously shown by Guillot et al, (2009). [39] Mulla et al (2012) observed that mental training alone cannot replace conventional training.…”
Section: Resultssupporting
confidence: 54%
“…Only two MI interventions could be classified in the age group 40 to 49 years [37,38]. The MI intervention described by Vergeer and Roberts was performed with healthy participants of both genders [37].…”
Section: Resultsmentioning
confidence: 99%
“…MITS elements resembled those of the average positive MI intervention, with group sessions and a multimodal approach for MI instructions ( written, visual and acoustic ). The second article, published by Guillot et al ., described an MI intervention with participants (male and female) who had burns [38]. The authors used added , individual , supervised and directed MITS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Motor imagery studies were conducted on several diseases relating to the central nervous system and acute injuries involving orthopedics such as subacute stroke [15][16][17][18][19], chronic stroke [20][21][22], traumatic brain injury [23], multiple sclerosis [23], shoulder impingement syndrome [24], postsurgical anterior cruciate ligament [25], postsurgical flexor tendon repair [26], burn injury [27], phantom limb pain [28], complex regional pain syndrome [28,29], and motor coordination problems [30]. Table 1 lists motor imagery clinical studies found in PubMed.…”
Section: Clinical Studies Of Motor Imagerymentioning
confidence: 99%